QUALITATIVE CHARACTERIZATION AND INDICATION OF INTROGRESSION IN FEMALE SIKUMBANG JONTI DUCKS IN SMALLHOLDER FARMS OF PADANG CITY - Teguh Rafian; Woki Bilyaro; Jonathan A. Lase (Universitas Muhammadiyah Malang, 2026)
This study aimed to analyze the frequency of qualitative phenotypic traits and estimate the introgression value in a population of female Sikumbang Jonti ducks reared in smallholder farms in Padang City, West Sumatra, Indonesia. A total of 44 sexually mature female Sikumbang Jonti ducks were selected using a purposive sampling method. The observed qualitative phenotypic traits included the color and shape of the bill, as well as the coloration of the head, neck, body, wings, thighs, tail, shank, and several other morphological characteristics. Data were analyzed descriptively using phenotypic frequency percentages, while the introgression value was estimated by comparing the phenotypic frequencies of the observed population with those of the original and donor populations. The results showed that several phenotypic traits exhibited dominant frequencies, including flat bill shape, brown eye color, absence of a neck ring, and horizontal body posture, each reaching 100%. Black bill color showed a frequency of 86.36%, while white head and neck coloration reached 90.91% and 88.64%, respectively. Phenotypic variation was observed in several plumage color traits, particularly the brown-white body coloration, which accounted for 59.09% of the population, indicating considerable phenotypic diversity within the population. The introgression value in the Sikumbang Jonti duck population was estimated at 16.90%, with an estimated phenotypic purity level of 83.10%. The study indicates the presence of phenotypic variation that may reflect possible introgression from introduced duck breeds, although molecular studies are required for confirmation.